Aberrant Expression of MicroRNA-15a and MicroRNA-16 Synergistically Associates with Tumor Progression and Prognosis in Patients with Colorectal Cancer - Guangfa Xiao; Huihuan Tang; Wei Wei; Jian Li; Liandong Ji; Jie Ge (Gastroenterology Research and Practice)
The aim of this study was to reveal the associations of microRNA miR-15a and miR-16 dysregulation with clinicopathological characteristics and prognosis in patients with colorectal cancer. As a result, we found that miR-15a and miR-16 expression, detected by quantitative real time-PCR, were both significantly downregulated in colorectal cancer tissues compared with adjacent colorectal mucosa (both P<0.001). Particularly, the expression levels of miR-15a in colorectal cancer tissues were positively correlated with those of miR-16 significantly (Spearman correlation coefficient r=0.652, P<0.001). In addition, miR-15a and/or miR-16 downregulation were all significantly associated with advanced TNM stage (all P<0.05), poorly histological grade (all P<0.05), and positive lymph node metastasis (all P<0.05). Moreover, the survival analysis identified miR-15a expression, miR-16 expression, and miR-15a/miR-16 combination as independent predictors of both unfavorable overall survival and disease-free survival. Interestingly, the prognostic value of miR-15a/miR-16 combination was more significant than miR-15a or miR-16 expression alone. Collectively, the aberrant expression of miR-15a and miR-16 could be used to stratify patients with aggressive tumor progression of colorectal cancer. The combined pattern of miR-15a and miR-16 downregulation has a significant value for distinguishing patients with a worse prognosis of colorectal cancer after surgery.